PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN REAKSI REDUKSI OKSIDASI KELAS X MIPA SMA NEGERI 12 PEKANBARU - Ahwi Solihin; Elva Yasmi Amran; Rajawali Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This research aimed to increase student achievement by application of active learning strategies types reviews style game Hollywood Squares on learning topic of Reaction On Reduction And Oxidation in X MIPA SMA N 12 Pekanbaru. This is an experimental research with randomized control group pretest-posttest design. Subject of this research are X MIPA-3 as the experimental class, X MIPA-4 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with the application of active learning strategies types Hollywood Squares Review while the control group without the application active learning strategies types Hollywood Squares Review. The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 3,51 and ttable = 1,66 with α=0,05, dk=69. tcount > ttable is 3,51 > 1,66, It’s mean that the application of active learning strategies types reviews style game Hollywood Squarescan improve students achievement on the subject of reaction on reduction and oxidation in X MIPA SMA Negeri 12 Pekanbaru.Key Word : Learning Achievment, Hollywood Squares Review, and Reaction of Reduction and Oxidation